2023
DOI: 10.1140/epjc/s10052-023-11274-8
|View full text |Cite
|
Sign up to set email alerts
|

The optical appearance of charged four-dimensional Gauss–Bonnet black hole with strings cloud and non-commutative geometry surrounded by various accretions profiles

Abstract: Thanks for the releasing image of supermassive black holes (BHs) by the event horizon telescope (EHT) at the heart of the M87 galaxy. After the discovery of this mysterious object, scientists paid attention to exploring the BH shadow features under different gravitational backgrounds. In this scenario, we study the light rings and observational properties of BH shadow surrounded by different accretion flow models and then investigate the effect of model parameters on the observational display and space-time st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…On the other hand, theoretical investigations of shadow images of compact objects are quite fascinating. This applies not only to black holes in General Relativity [36][37][38][39][40][41][42][43][44][45] and in alternative gravities [46][47][48][49][50][51][52][53][54][55][56], but also to exotic compact objects like wormholes [57][58][59][60][61][62][63][64][65][66][67], naked singlarities [68][69][70][71][72][73][74][75][76][77][78] or boson stars [79,80]. Previous studies have shown that some of these exotic compact objects can mimic black holes with respect to their shadow images if their light ring properties are similar.…”
Section: Jcap05(2024)007mentioning
confidence: 99%
“…On the other hand, theoretical investigations of shadow images of compact objects are quite fascinating. This applies not only to black holes in General Relativity [36][37][38][39][40][41][42][43][44][45] and in alternative gravities [46][47][48][49][50][51][52][53][54][55][56], but also to exotic compact objects like wormholes [57][58][59][60][61][62][63][64][65][66][67], naked singlarities [68][69][70][71][72][73][74][75][76][77][78] or boson stars [79,80]. Previous studies have shown that some of these exotic compact objects can mimic black holes with respect to their shadow images if their light ring properties are similar.…”
Section: Jcap05(2024)007mentioning
confidence: 99%
“…This makes it feasible to analyze the observational characteristics of BH shadows surrounded by different accretion flow models. In the mechanism of different theories, the study of BH shadow and its observational appearance along with other significant properties have also been analyzed in [36][37][38] and many other associated works exist in literature. Nowadays, a number of researchers have devoted themselves to exploring the physics of BH images and trying to achieve remarkable results, which told a comprehensive story of BH in our Universe.…”
Section: Jcap11(2023)013mentioning
confidence: 99%
“…Assuming an optically thin disk accretion flow model, Gralla et al [20] discussed the BH shadow and the photon rings of Schwarzschild BH and found that the luminosity of the ring diverges logarithmically at the position of the photon ring. Zeng et al [21] analyzed some interesting features of the charged four-dimensional Gauss-Bonnet BH, considering the strings clouds and non-commutative (NC) geometry under different accretions flow models. Saleem and Aslam [22] investigated the optical features of a charged NC Kiselev BH through different configurations of accretion matter.…”
Section: Introductionmentioning
confidence: 99%